Peran dan Fungsi Advokat sebagai Penegak Hukum - Raihan Baihaqi; Hasrat Dihati; Fauziah Lubis (Journal on Education, 2023)
The purpose of this research is none other than to be able to provide input on the integrity of advocates, who are free and independent and cannot be separated from their responsibilities based on a code of ethics. Law enforcement issues in Indonesia are always an interesting topic to discuss. Law enforcement, which from the beginning was only a process that did not find a final result, has led to good discussion in formal and non-formal studies. The discrepancy between expectations and the reality of the operation of the law causes law enforcement to be questioned again, the law has not yet found its true purpose. Factors that are non-legal in nature are suspected as causes that have an impact on discriminatory law enforcement, inconsistency and uncertainty (unjust) which in the end lead to disharmony in society towards the law, especially law enforcement officials. The approach in this legal research uses statutory and conceptual approaches. In addition, the conclusion obtained is that advocates should maintain their integrity as an advocate and behave according to the advocate's code of ethics. However, upholding the code of ethics has so far experienced many obstacles in its enforcement, especially in the absence of a single forum for advocate organizations that is strictly and clearly regulated.